UTILIZATION OF SALINE MUD FLATS FOR FISH CULTURE-AN EXPERIMENT IN MARINE FISH FARMING - Tampi, P R S (Indian Journal of Fisheries, 2015)
Scope for economically feasible fish farms in brackish water areas in India has long been realised and practically demonstrated by the numerous fish and prawn farms adjoining the backwaters of Cochin along the west coast. Apart from these even some of the other low-lying saline coastal mud flats of the south-east coast of the Indian Peninsula, which periodically get flooded with sea water but usually with a relatively low biological productivity owing to certain inherent ecological drawbacks, also show potentiaUties for development. Attempts at fish culture in similar marine environments have not been many in this country except for the earlier enterprises by the Madras Fisheries Department as reviewed by Chacko and Mahadevan (1956). A project was recently undertaken at the Central Marine Fisheries Research Station in order to determine to what extent these apparently low productive areas can be brought under more effective utilization for fish culture purposes and the preliminary results are given in this account.